Monolingualism and its meaning in two KwaZulu-Natal high schools - Carlyle, Jacqui (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2017)
This study reports on the identity and attitudes of monolingual English speakers (MES) at two high schools in Durban, South Africa, in relation particularly to the role and meaning of monolingualism. Two bodies of data are used to investigate the attitudes of MES and are oriented towards four variables: English, African languages (particularly Zulu), monolingualism and plurilingualism. The attitudes to these variables reveal the impact on identity of language usage in Durban, and negotiations of the participants in trying to mitigate or justify attitudes that are counter to the embracing of diversity encouraged in modern South Africa. First, an attitude questionnaire provides quantitative data that is subjected to analysis, including a chi-squared test. Second, a narrative elicitation interview provides qualitative narrative data that is analysed in relation to APPRAISAL theory. Both analysis types are used to ascertain the presence of a monolingual mindset in the scholars' responses, as well as to capture the ideological forces to which they are subjected as monolingual English speakers in the unique multilingual setting of Durban. In essence, the data points to a discourse of compromise and unease on the part of the participants - as they juggle with the effects of an English-centric monolingual mindset, and a more pervasive pluralism that embraces the Rainbowism of 'the new South Africa'. This discourse of compromise is characterized on one side by insecurity and dissatisfaction with the language in education policy, and well as the monolingual upbringing of MES in Durban, and a lack of Language other than English (LOTE), in particular, Zulu. This side of the compromise also portrays a pro- plurilingual orientation, a positive valuation of knowing a LOTE and of plurilingual people. Here, however, the manifestation of the 'other side' of the compromise appears as the MES characterize plurilingualism as exceptional and too difficult, and language learning at school as having a negative impact on academic success. Alongside this is a normalization of English and othering of African languages in practical situation. English is also promoted as the language of unity and economic and academic progress or success, while the material value of African languages is questioned.
Keywords: Monolingualism -- South Africa; Monolingualism -- South Africa -- Case studies; Language awareness -- South Africa; Language and education -- South Africa; School children -- South Africa -- Attitudes; School children -- South Africa -- Attitudes -- Case studies; African languages -- Study and teaching -- South Africa -- Attitudes